The use of a mental imagery intervention to enhance integrated regulation for exercise among women commencing an exercise program - Duncan, Lindsay R.; Hall, Craig R.; Wilson, Philip M.; Rodgers, Wendy M. (Motivation and emotion, 2012)
The purpose of this study was to examine the effects of a mental imagery intervention designed to enhance integrated regulation for exercise among women commencing an exercise program. Healthy women who previously did not exercise regularly ( N = 102; M age = 29.54, SD = 8.34) participated in an 8-week cardiovascular exercise program in which they exercised 3 times each week at a moderate intensity. The intervention group ( n = 51) received weekly guided imagery sessions which were administered in person via audio recording. A comparison group (i.e., attention control; n = 51) received health information delivered in the same manner. Despite substantial dropout of participants from both groups, the analysis revealed that participants in the imagery group experienced greater changes in integration than participants in the comparison group. These findings support the utility of imagery interventions for influencing exercise-related cognitions, and more specifically integrated regulation.